A Retrospective Analysis of Lower Thoracic Spinal Anesthesia for Laparoscopic Cholecystectomy - Luiz Eduardo Imbelloni; Marcos Fornasari; Raphael Sant’Anna; Geraldo Borges de Morais Filho (Medicine and Medical Research: New Perspectives Vol. 5, 2024)
Background: Laparoscopic surgery is normally performed under general anaesthesia, but regional techniques have been found beneficial, usually in the management of patients with major medical problems. In the study group, following evidence that spinal anesthesia is safe compared to general anesthesia, spinal anesthesia has become the preferred technique for this procedure. Aim: This retrospective study highlights laparoscopic cholecystectomy under thoracic spinal anesthesia. Methods: A total of 505 laparoscopic cholecystectomy patients operated under spinal anesthesia were included in this study. Spinal anesthesia was between T8 to T11, with a 27G cutting point or pencil tip in lateral or sitting. Spinal anesthesia was performed with two doses of 0.5% bupivacaine hyperbaric plus 25 µg of fentanyl, until reaching the sensitive level of T3. The study evaluated the demographics, analgesia, and degree of motor block, incidence of paresthesia, bradycardia, hypotension, anesthesia success and neurological complications. Results: All 505 patients developed spinal anesthesia. Neither the dose of hyperbaric solution of 0.5% bupivacaine nor the addition of fentanyl affected the onset of sensory block. The duration of the sensory block was greater than the motor block with a hyperbaric solution. Bradycardia occurred in 16 (3.1%) patients and was not correlated with the level of thoracic puncture. Hypotension occurred in 82 (16.2%), with no significant association with the dose of local anesthetic. None of the 505 patients had the maximum degree of lower limb motor block, with significant differences in terms of dose. Paresthesia was observed in 28 (5.5%) without significant differences between needles. All paresthesias were transient and without residual sequelae. The creation of the pneumoperitoneum is an essential component of laparoscopic procedures. The insufflation of gas into the peritoneal cavity and increased intraabdominal pressure can cause several cardiocirculatory and pulmonary effects. Conclusion: The beginning of the block is fast regardless of the solution used. By providing a sensory block of longer duration than the motor block hyperbaric bupivacaine is reflected in a better indication. Thoracic spinal anesthesia provides excellent anesthesia for lower limb orthopedic surgery, without neurological sequelae. TSA provides hemodynamic stability with low need for vasopressors, without the appearance of hypoxemia or hypercarbia, without the need for an orogastric tube, and moving from the operating table to the stretcher without assistance, and with excellent analgesia for up to 6 hours and can be used on an outpatient basis.